Transfer of Copyrights on The Issues of Plagiarism in Review of Civil Law - Taufan Nalendra (IHSA Institute, 2021)
The increasing era of globalization has had an impact on various sectors of life, one of which is the search for various sciences that can develop human potential, but behind the ease of accessing various information, there is an act of plagiarism that is very dangerous for every work and writing of others. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that, plagiarism activities are a crime that exists in any field, in fact these activities are commendable actions and are against the law, in Indonesian positive law, plagiarism activities are included in category of criminal law crime and can be rewarded with various sanctions ranging from the threat of monetary fines and imprisonment, plagiarism can also reduce the morals and dignity of others, and have an impact on the disintegration of the academic community because the act of quoting without permission must be prevented and if it occurs it must addressed as early as possible, there are many actions that are classified as plagiarism activities, ranging from quoting, plagiarizing, selling and changing the contents of the writing, intentionally and without official permission from the original author.